On the teaching of world history in English on the condition of imperfect language skills - Syzdykova, A.M.; Shirokova, Zh.K. (Ye.A.Buketov Karaganda State University Publ., 2015)
Present makes high demands for schools and universities graduates; one of the requirements is to speak several languages. The article shows the problem of implementation of multilingual and multicultural education. In the authors' opinion, teaching and learning historical subjects in a foreign language will allow to solve these problems successfully. In terms of the abovementioned authentic texts have a particular importance in language training students. The article considers some types of authentic texts and kinds of reading necessary for teaching foreign languages for future teachers of the world history.
Ағылшын тілін жетік білмейтін топтарда дүниежүзі тарихын ағылшын тілінде оқытудың кейбір мəселелері
К вопросу преподавания всемирной истории на английском языке в условиях несовершенного владения языком
Keywords: education; multilinguism; history teaching; authentic texts